Tax rate and tax base competition for foreign direct investment - Peter Egger; Horst Raff (Kiel Institute for the World Economy (IfW), 2011)
This paper argues that the large reduction in corporate tax rates and only gradual widening of tax bases in many countries over the last decades are consistent with tougher international competition for foreign direct investment (FDI). To make this point we develop a model in which governments compete for FDI using corporate tax rates and tax bases. The model's predictions regarding the slope of policy reaction functions and the response of equilibrium tax parameters to trade costs and market size are shown to be consistent with panel data for 43 developed countries and emerging markets. Using estimated policy reaction functions we simulate the effect of regional trade integration and find that this integration has contributed significantly to the observed fall in corporate tax rates.
Keywords: F15; F23; H20; H25; 330; corporate taxes; tax competition; foreign direct investment; multinational firms; free-trade areas; regional integration